Analysis of the Suppression Device as Vortex Induced Vibration (VIV) Reducer on Free Span using Finite Element Method - Priyanta, Dwi; Abdullah, Anang (International Journal of Marine Engineering Innovation and Research, 2025)
Subsea pipeline is a transportation infrastructure of oil and gas as an alternative for ship tanker. The uneven topography surface of the sea floor resulting the pipe undergoes free span. The free span is a condition endured by the pipe where the pipe position has distance or gap with the seabed supported by two pivot. The free span is at risk of experiencing a vibration caused by the presence of dynamic load that is current and the wave. The vibration that occurs is the impact of the presence of the phenomenon of Vortex Induced Vibration (VIV). The Phenomenon Of VIV occur on a cylindrical component caused by ocean currents, causing the occurrence of vibration by the movement of fluid on the pipe so that it raises the vortex at the rear of the direction of oncoming flow. One way to dampen or reduce the impact of VIV is by adding suppresion device. VIV suppression device is a tool that is installed on the pipeline on offshore piping installationcthat serves to dampen or reduce the impact of VIV. One of the simulations used to know the characteristics of a fluid is to use (CFD) Computational Fluid Dynamic. With the addition of suppression device can add the rest of the operating time on a free span of affected VIV, on the condition of free span critical exposed VIV (Vortex Induced Vibration value) has a life time on plain pipe 44.21 years, on pipe with 53.09 years and Fairing on the pipe with the Helical strike 52.95 year.